Rural Entrepreneurship In Iran - Ebrahimi, Mohammad Sadegh; Baniasadi, Neda; Khatonabadi, Seed Ahmad (Journal of Rural Indonesia [JORI], 2013)
"Entrepreneurship" is a process which takes place in a network in the presence of social relations. Vast majority of the studies related to entrepreneurship have been in the form of personality traits of the entrepreneurs and paying attention to social networks and social capital, has been neglected by them. This study investigates the rural entrepreneurship in Iran and the cases of the study are some villages in the county of Kerman. The research method is library work and field study. After defining the indexes and variables of the study through a questionnaire, the necessary data are gathered. The sampling population is estimated 150 rural enterprises in the county of Kerman. The research findings show that there is a direct and significant relationship between rural entrepreneurship and social capital, entrepreneurship and correlation, entrepreneurship and awareness, entrepreneurship and cooperation. In the factor analysis of entrepreneurship, entrepreneurship infrastructures have the highest effect on the process of entrepreneurship. Â© 2013 Journal of Rural Indonesia [JoRI] IPB. All rights reserved.Keywords: Â entrepreneurship, social capital, rural areas, social networks, factor analysis, iran.